The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15244/pjoes/66768
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectral Analysis of the Aged 1,3,5-Trimethylbenzene Secondary Organic Aerosol in the Presence of Ammonium Sulfate Seeds

Abstract: The ammonium sulfate ((NH 4 ) 2 SO 4 ) seed aerosols commonly found in the Chinese urban atmosphere could affect the formation and aging of secondary organic aerosols (SOA). Aging of aromatic SOA is performed using UV-irradiation of 1,3,5-trimethylbenzene (135-TMB)/CH 3 ONO/NO/air mixtures with high concentrations (~100 μg/m 3 ) of (NH 4 ) 2 SO 4 seeds in the laboratory chamber in this study. The particulate products of SOA were measured using an aerosol laser time-of-flight mass spectrometer (ALTOFMS) in real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The reaction products were characterized by UV-visible spectroscopy, infrared spectroscopy and time-of-flight mass spectrometry. The series of characteristic mass spectral peaks C x H y N n + of imidazole nitrogen-containing organic compounds of aromatic SOA were obtained, and it was confirmed that imidazole nitrogen-containing compounds formed from the heterogeneous reaction of NH 3 and dicarbonyl components of aromatic SOA [22][23][24]. On this basis, this paper continues to study the effects of different ingredients, concentrations, humidity and acidity of seed aerosol on the formation of nitrogencontaining organic compounds formed from the reaction of NH 3 with the photooxidation products of toluene.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…The reaction products were characterized by UV-visible spectroscopy, infrared spectroscopy and time-of-flight mass spectrometry. The series of characteristic mass spectral peaks C x H y N n + of imidazole nitrogen-containing organic compounds of aromatic SOA were obtained, and it was confirmed that imidazole nitrogen-containing compounds formed from the heterogeneous reaction of NH 3 and dicarbonyl components of aromatic SOA [22][23][24]. On this basis, this paper continues to study the effects of different ingredients, concentrations, humidity and acidity of seed aerosol on the formation of nitrogencontaining organic compounds formed from the reaction of NH 3 with the photooxidation products of toluene.…”
Section: Introductionmentioning
confidence: 61%
“…1. The mass spectrum peak with the highest peak intensity of m/z 41 (C 2 H 2 N + ), along with m/z 67 (C 3 H 3 N 2 + ) and 28 (CH 2 N + ) are the characteristic cracking peaks of the imidazole compounds, indicating that the nitrogen-containing imidazole organic compounds are the main reaction product [22][23][24]. In addition, in the mass spectrum, the fragment peak of m/z 18 corresponds to the ammonium ion (NH 4 + ), and m/z 44 is the fragment peak (COO + ) after the carboxyl group (-COOH) of the organic acid compound loses the hydrogen atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an important contributor to SOA in urban areas, aromatic hydrocarbons are generally concerned about their kinetics (Atkinson and Arey, 2003;Calvert et al, 2002), reaction mechanisms (Tsiligiannis et al, 2019;J. Midey * et al, 2003;Huang et al, 2017c;Wang et al, 2020;Garmash et al, 2019), SOA yield (Cao and Jang, 2007;Kroll et al, 2007;Ng et al, 2007b;Huang et al, 2017b), ozone generation potential (Luo et al, 2019), and SOA physicochemical properties (optical properties, morphology, etc.) (Grosjean, 1981;Li et al, 2018;Li et al, 2017b;Phillips and Smith, 2014;Kim and Paulson, 2013;Huang et al, 2018).…”
mentioning
confidence: 99%